Structural characterization and immunostimulant activities of polysaccharides fractionated by gradient ethanol precipitation method from Panax ginseng C. A. Meyer - Xu, Mengran; Ren, Jing; Jiang, Ziye; Zhou, Shuo; Wang, Enpeng; Li, Hui; Wu, Wei; Zhang, Xiaoyu; Wang, Jing; Jiao, Lili (Frontiers in Pharmacology, 2024)
Panax ginseng C. A. Meyer is a dual-purpose plant for medicine and food, its polysaccharide is considered as an immune enhancer. Four polysaccharides, WGP-20-F, WGP-40-F, WGP-60-F and WGP-80-F were obtained from ginseng via water extraction and gradient ethanol precipitation with different molecular weights (Mw) of 1.720 × 10 6 , 1.434 × 10 6 , 4.225 × 10 4 and 1.520 × 10 4 Da, respectively. WGP-20-F and WGP-40-F which with higher Mw and a triple-helix structure are glucans composed of 4-ɑ-Glcp, do not show remarkable immunoregulatory effects. WGP-60-F and WGP-80-F are heteropolysaccharides mainly composed of 4-ɑ-Glcp and also contain t-ɑ-Araf, 5-ɑ-Araf and 3,5ɑ-Araf. They are spherical branched conformations without a triple-helix structure and can effectively increase the index of immune organs, lymphocyte proliferation, activate macrophages to regulate the immune system in mice and further enhance immune functions by improving delayed-type hypersensitivity reaction and antibody response. These results indicated that WGP-60-F and WGP-80-F could be used as potential immune enhancers, and gradient ethanol precipitation can be applied for the preparation of ginseng bioactive polysaccharide.